Peran Guru dalam Mewujudkan Keterampilan Vokasional Memanfaatkan Barang Bekas secara Kreatif bagi Anak Tunagrahita pada Masa Pandemi Covid-19 di Sekolah Luar Biasa C Karya Tulus - Paulinus Tibo; Maria Elpina Padang; Regina Sipayung (Jurnal Penelitian Pendidikan Agama Katolik, 2022)
The role of teachers in special schools is very important for mentally retarded children. In mentoring these teachers, all teachers take part in real terms in the form of attendance and duty. The participation of teachers in their duties, for example as classroom teachers, assisting mentally retarded children in utilizing used vocational skills, encouraging the creativity of mentally retarded children to provide examples of used goods with simple practices and bringing mentally retarded children to study outside the classroom to use used goods and so on. The participation of these mentally retarded children cannot be separated from the role of the class teacher. The teacher's role is not only as a mentor, creativity booster, and innovator, but there are so many roles that a teacher needs to teach in an extraordinary school. This study uses a qualitative approach with data collection techniques such as observation, interviews, and documentation. In this study, it appears that during the Covid-19 pandemic, the role of the teacher has not disappeared but has taken on the task well to increase the use of used goods with vocational skills activities in schools.